Evidence from a Systematic Literature Review on Digital Games and Language Learning in Childhood - Nyak Mutia Ismail; Rosmiati Rosmiati; Ida Fitria; Alsabarni AMD (Yayasan Keluarga Guru Mandiri, 2026)
Over the last few years, scholars have shown increasing interest in using digital game-based learning in early childhood and primary education. It is a systematic literature review that adhered to PRISMA 2020 to integrate empirical research studies published 2020-2025, and used Scopus as the primary database. Originally, 70 studies were found in the search. Duplicate removal and eligibility screens for abstracts and full texts enabled the inclusion of 24 studies in this review. The methodological attributes and substantive findings were taken into account during data extraction. DGBL was observed to enhance sustained motivation in children, which triggered a quantifiable increase in language and literacy. Its effects were positive on vocabulary learning, phoneme-grapheme mapping, grammarreinforcement, and productive sharing, also in children with developmental challenges. Digital not only supports executive functions but also fosters computational literacy, transcending linguistic boundaries. The mediating variables were L1 orthographic transparency, intervention duration, adult scaffolding, and cultural correspondence. Though this synthesis addresses a gap in the inherited consolidation of new evidence, several limitations remain due to the insufficient length or time of most interventions and a skills-focused orientation. To achieve this, future research should adopt longitudinal designs, multi-dimensional literacy scales, and culturally sensitive methods.